Design of a Dual-Band Frequency Reconfigurable Patch Antenna Based on Characteristic Modes - Zakaria Mahlaoui; Eva Antonino-Daviu; Adnane Latif; Miguel Ferrando-Bataller (International Journal of Antennas and Propagation)
A frequency reconfigurable patch antenna design based on the characteristic mode analysis is presented. The antenna presents a reconfigurable lower band and a steady band at higher frequencies. A slot is etched on the ground plane of the antenna, where two varactor diodes are placed on each side of the slot in order to tune the lower band. The first resonant frequency shifts down by varying the reverse voltage of the varactor, whereas the second operating frequency keeps stable. The proposed antenna is designed to cover WLAN bands, offering a first band operating at 2 GHz and a second band ranging from 5.3 GHz to 5.8 GHz. A prototype has been fabricated and measurements are provided, which validate the proposed analysis, method, and design procedure.